Fractal leadership : ideologisation from the 1960s to contemporary social movements - Karatzogianni, Athina; Matthews, Jacob (Emerald Publishing Limited, 2023)
Fractal Leadership investigates leadership construction in social movements afforded (or intensified) by algorithm-based flows of information and viral affectivity. The book illustrates how a somewhat amorphous structure is replicated from an intimate, localised community level, all the way up to the global level with swift, almost breath-taking repetitions over and over again, from one scale to another, thus carrying new forms of leaders to sudden public mass-following, but just as quickly sweeping them away. Including original primary research with fieldwork from Extinction Rebellion and Black Lives Matter in juxtaposition with archival research of the New Left movements of the 1960s, Karatzogianni and Matthews explore how the digital transformation of temporality impacts on the ideologisation process, movement organisational structure, as well as the implicated biolabour process, culminating on the fractalisation of movement leadership and its devastating implications for class formation, and the authoritarian turn in global politics. Fractal Leadership serves as a point of reference for those interested in tracing the development of leadership in social movements from the 1960s to today.
Includes index.
Keywords: Social movements.; Political leadership.; Communication and technology.; History -- Social History.; Demonstrations & protest movements.; elektronické knihy; electronic books